How to Increase Sales by Strengthening Online Social Networking - Pratami, Wijaya Ni Putu Nurwita (CENTRAL ASIA AND THE CAUCASUS, 2022)
The current pandemic conditions force every company to think about how to survive in the industry. The digitalization process occurs in almost all industrial sectors. Things that have an impact on the condition can also be seen from changes in people's lifestyles online. The purpose of this study is to take a deeper look at social networking and the benefits that companies feel when using it as a marketing strategy. The sample of this study is the community of social media users. This type of research is descriptive with a sample of 30 respondents.